The protective effect of celery (Apium graveolens L.) ethanol extract on anemia in 5/6 subtotal nephrectomy rat model - Afifah Afifah; Khusnul Muflikhah; Tri Lestari; Eman Sutrisna; Ajeng Kirana; Sindy Devi Prastiwi (Universa Medicina, 2020)
BackgroundAnemia is a frequent complication of chronic kidney disease (CKD). Anemia in CKD is associated with reduced quality of life, increased cardiovascular disease, cognitive impairment, and mortality. Therefore it is necessary to find an alternative agent for preventing anemia in CKD. Celery is one of the natural substances that have anti-inflammatory, antioxidant, and antihypertensive pharmacological effects. Based on the mechanism of CKD and its progression, celery is thought to prevent anemia in CKD. This research was aimed at evaluating the protective effect of celery extract against anemia in a CKD rat model. MethodsThis was an experimental laboratory study using 25 male Sprague Dawley rats, aged 2-3 months, they were randomized into 5 groups, namely group A, sham operation; group B, subtotal nephrectomy; group C, D, E, subtotal nephrectomy + 250, 500, 1000 mg/kg BW ethanol extract of celery, respectively. The administration of celery extract was performed 14 days before and 14 days after induction of 5/6 subtotal nephrectomy. The hematological parameters (Hb, RBC, Ht, MCV, MCH, MCHC) and serum creatinine level were measured at the end of the study. Data were analyzed with One Way ANOVA and Kruskal-Wallis test followed by Mann-Whitney test at p<0.05. ResultsThere were no significant differences between groups in Hb, RBC, Ht, MCV (p>0.05) and significant differences between groups in MCH and MCHC (p<0.05). The highest levels of Hb, RBC, and Ht were found in group C.ConclusionCelery ethanol extract at a dose of 250 mg/kg BW/day may prevent anemia in the CKD rat model.